Liberdade de expressão artística e o espaço público: uma interpretação constitucional - Buchiniani, Rodrigo Guimarães (2016)
After the more than twenty seven years of existence of the 1988 Brazilian Federal Constitution which interrupted, since the beginning of the Republic in 1889, a long period of countless limitations of the individual and artistic liberties, to ensure through all of the text the effectiveness of making art to be the duty of the State and the right of the citizen to express oneself and to artistically interfere in the day-to-day of society upon stimulating or repressing behaviors. The dissertation covers the Fundamental Right of Freedom of Artistic Expression in public space and has, as a starting point, the actual Constitution of 1988 to verify the amplitude of the devices that are directly or indirectly related to making art that for an aspect to ensure the free initiative of the artist and, as another point, it indicates possible limitations. Based on the constitutional hermeneutics as a tool of dialogue so that, with general and abstract language, characteristics of the constitutions, of the text upon unveiling other possibilities of constitutional interpretation and of a possible theoretical application for the maintenance of juridical stability and order because of the evaluative content of the constitutional guarantee of freedom of artistic expression. Beyond being one of the formative elements of the Brazilian People, the culture revealed in artistic expression assumes, in the social context and in the public space, the maximum force of a free, plural, and democratic country